(untitled) (Applied Biological Research, 2018)
Yield and juice quality of 16 sugarcane clones, procured from Sugarcane Research Institute, DRPCAU, Pusa, Samastipur, Bihar (India), was evaluated under waterlogging stress condition during 2016 to 2017. The trials were laid out in a randomized block design with three replications. The depth of water was 130 cm for 15 days of August. The experimental plot remained waterlogged during June-September 2016 varied from 30 to 90 cm. Three budded sets from upper half of the canes were used for planting. Planting was done following full agronomic and plant protection practices recommended for North Bihar (India) conditions. The result revealed high heritability coupled with high genetic advance, as per cent of means, for cane yield, leaf area index at 30 days after waterlogging, leaf area index before waterlogging, leaf area index at 60 days after waterlogging and sugar yield suggesting the preponderance of additive genetic effect in the determination of these traits. It also indicated that selection for these traits will be effective if desired improvement is to bring for cane and sugar yield under waterlogged condition. Ranking of clones based on selection index and three other criteria revealed that clone CoP2061 was the most suitable clone among the clones studied. The clone can directly be used as varieties for waterlogging tolerance and may be used in crossing programme as parents to develop waterlogging tolerant clone.